Essays on banking in the post-crisis era - Tracey, B (2016)
This thesis aims to advance our understanding of banking in the post-crisis era. It makes three distinct contributions to the literature on banking. The first chapter examines whether "too-big-to-fail" (TBTF) factors affect estimates of scale economies for large banks. Based on a standard model of bank production that does not control for any TBTF factors, we find evidence of scale economies for our sample of large banks. However, once we control for TBTF factors, we instead find evidence of constant returns to scale. These results suggest that estimates of scale economies for large banks are affected by TBTF factors. The second chapter examines the impact of forbearance lending on firm dynamics and performance in Europe since the sovereign debt crisis. We develop a quantitative model, which features endogenous forbearance lending and endogenous firm defaults, as well as information asymmetry faced by the lender. We fit the model to key Euro Area firm statistics over the period 2011 to 2014. We show that in the absence of forbearance lending, the average firm sales growth, investment and productivity are higher than in the benchmark scenario with forbearance lending. These results suggest that forbearance lending practices have contributed to the recent economic stagnation across the Euro Area. The third chapter introduces a novel way to identify the causal effect of bank capital on risk-taking. We use provisions for misconduct issues as an instrument for bank capital. We show that misconduct provisions are an appropriate instrument due to their strong and negative impact on bank capital, and are otherwise unrelated to asset risk-taking. Our main finding is subsequently that a negative shock to bank capital leads to an increase in risk-taking, as measured by detailed information on mortgage underwriting standards.